Notes on platymonas impellucida (McLachlan & Parke) species in mono-algal cultures - Mihnea, Pia Elena (Cercetări Marine - Recherches Marines, 2026)
A new species found In the Black Sea, Platymonas lmpelluclda McLachlan & Parke, is described. Were analyzed the rhythms of its growth in culture conditions. Nine variants of the same culture medium were used; the environmental conditions were maintained constant and Identical for each alternative. It was attempted a comparison of natural populations with the experimental ones, and the data regarding differences found were discussed.